Situasi Kebahasaan pada Lanskap Linguistik di Masjid Tiban Malang: Linguistics Lanscape in Masjid Tiban Malang - Gya Nindya Handini; Halimatun Nashihah; Isna Novidah Al Khumairo; Kamal Yusuf (Universitas Ahmad Dahlan, 2021)
This study investigates the phenomenon of the public linguistic landscape, which reveals the use of language in the Tiban Mosque in Malang, East Java. The goal of this research was to describe the language contestation practiced in the Tiban mosque. Furthermore, the purpose of this research is to describe the function of language in the linguistic landscape at the Tiban Malang mosque. The collected data was then classified as monolingual, bilingual, or multilingual. The qualitative descriptive method is used in this linguistic landscape study. Data is collected by observing the location, photographing the object building, and documenting it. According to the findings of this study, the linguistic landscape in the vicinity of the Tiban Malang Mosque is dominated by monolingual and bilingual speakers. This is used to make it easier for visitors and tourists to visit the Tiban mosque's religious tourism area.